Pengembangan Flash card Berbasis Budaya Lokal Bangka Belitung Sebagai Media Literasi Keuangan Anak Usia Dini - Zonalisa Fhatri; Diah Novianti; Wulan Naroh (Institut Agama Islam Negeri Madura, 2026)
This study aimed to develop local culture–based flash cards from Bangka Belitung as a learning medium to support financial literacy among early childhood students. The study employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model using a Research and Development (R&D) design involving 40 children aged 5–6 years from two early childhood education institutions in the Bangka Belitung Islands Province. Data were collected through structured observations, expert validation questionnaires, and pretest–posttest assessments. The results indicated that the developed media achieved a very high level of feasibility, with material expert validation reaching 92% and media expert validation 89%. Limited trials demonstrated a significant improvement in children’s financial literacy scores, increasing from an average of 56.4 on the pretest to 84.7 on the posttest, reflecting a gain of 28.3 points (50.17%). Children’s engagement during the learning process reached 85% based on structured observational data. These findings indicate that the use of local cultural context within the learning media effectively enhances children’s understanding of key financial literacy concepts, including needs versus wants, the function of money, and saving habits. This study contributes a validated culture-based financial literacy learning model that is ready for broader implementation in early childhood education settings, with potential for further development in terms of interactivity and expanded effectiveness testing.